Observations of atmospheric ozone - 38 to 76 deg north latitude at altitudes from 8 km to the surface - Gregory, G. L.; Beck, S. M.; Hudgins, C. H. (1984)
Ozone data were obtained from 8 km to the surface and at latitudes from 38 to 76 deg N during January and February 1983. Flight lines covered northeastern U.S., Canada, and Greenland. The results of the latitudinal survey at 5- to 8-km altitude showed O3 mixing ratios to be about 40 ppbv with little variation in latitude. One region of elevated O3 was observed and extended from 54 N to 57 deg N latitude. Ozone reached 150 ppbv at 6.4-km altitude. This sampling was stratospheric air as the tropopause height was 5.6-km altitude. Profiles at 76, 67, and 53 deg N showed O3 to be be well mixed from about 5 km to the surface. In some cases, profiles identified a layer of 1 km to 100 m vertical dimension at the surface, in which O3 destruction had occurred.